ANALISIS PENGARUH JUMLAH UANG BEREDAR (M1), SUKU BUNGA SBI, NILAI TUKAR SUKU BUNGA DEPOSITO TERHADAP TINGKAT INFLASI - Fadli Ferdiansyah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
Inflation is one of the effects of a prolonged economic crisis that hit the country. Inflation is a situation where there is an increase in general prices which continuesover the long term. The purpose of this study was to determine the effect of the money supply, interrst rate, deposit interest rate and exchange rate (Rp/USD) of the inflation in 2006 – 2011.6 The result of this study suges that the suppy of money have no significant positive effect on inflation. SBI rate have positive and significant effect on inflation. Deposit have rate and no significant negative effect on inflation. Exchange Rate have no significant negative effect on inflation.Keywords : Money Supply, Interest Rates, Deposit Interest Rates, Exchange Rate (IDR /USD), Multiple Linear Regression, Inflation